Ceftriaxone-associated dysbiosis decreases voriconazole bioavailability by upregulating intestinal P-glycoprotein expression through activation of the Nrf2-mediated signalling pathway - Wang, Xiaokang; Ye, Chunxiao; Yang, Xixiao; Yang, Maoxun (Frontiers in Pharmacology, 2025)
ObjectivesThe purpose of this study was to investigate the effect of intestinal dysbiosis on the bioavailability of voriconazole and to explore any underlying mechanisms.MethodSprague-Dawley rats were randomly divided into two groups: a normal control group and a ceftriaxone-associated dysbiotic group. The composition of the intestinal flora was examined using 16S rRNA sequencing analysis. Voriconazole concentrations were determined by high-performance liquid chromatography-tandem mass spectrometry. Outer membrane vesicles (OMVs) of microbes from the different groups were prepared for in vitro study in Caco-2 cells. The Nrf2 pathway and its related proteins involved in modifying P-glycoprotein (P-gp) expression were clarified by a series of immunoblot analyses.Key findingsThe diversity and richness of intestinal bacteria, especially the abundance of gram-negative bacteria, were significantly decreased after ceftriaxone treatment. The AUC(0-t) and Cmax of voriconazole were reduced, and greater voriconazole clearance were noted in the dysbiotic group. An in vivo study also indicated that the expression of P-glycoprotein was significantly increased after ceftriaxone treatment, which may be due to the absence of gram-negative bacteria in the intestine. Finally, in vitro findings in Caco-2 cells treated with OMVs from the ceftriaxone-associated dysbiotic group suggested that Nrf2 translocation into the nucleus induced high expression of P-gp.ConclusionOMVs from intestinal bacterial in the ceftriaxone-associated dysbiotic group induced high P-gp expression by regulating the Nrf2 signalling pathway, which led to an in vivo reduction in the bioavailability of voriconazole due to ceftriaxone-associated dysbiosis.